2010
DOI: 10.1177/0022429410369836
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Perceived Pedagogical Utility of a Weighted Music Performance Assessment Rubric

Abstract: The purpose of this study was to investigate the reliability and perceived pedagogical utility of a multidimensional weighted performance assessment rubric used in Kansas state high school large-group festivals. Data were adjudicator rubrics (N = 2,016) and adjudicator and director questionnaires (N = 515). Rubric internal consistency was moderately high (.88). Dimension reliability ranged from moderately low (W = .47) to moderate (W = .77). Total score reliability was moderately high (W = .80) and rating reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 15 publications
6
46
0
Order By: Relevance
“…Norris and Borst (2007) found that interrater reliability was stronger for individual categories (e.g., tone, intonation, technique) and final scores when judges evaluated choral ensembles using a rubric with detailed descriptions for each possible score (1-5) in all categories as opposed to a traditional form with no category descriptions. Nonetheless, reliability for categories at largegroup festivals in Kansas varied from .47 (other) to .77 (tone), even with descriptors for each level of achievement (Latimer, Bergee, and Cohen 2010).…”
Section: Reliabilitymentioning
confidence: 96%
See 1 more Smart Citation
“…Norris and Borst (2007) found that interrater reliability was stronger for individual categories (e.g., tone, intonation, technique) and final scores when judges evaluated choral ensembles using a rubric with detailed descriptions for each possible score (1-5) in all categories as opposed to a traditional form with no category descriptions. Nonetheless, reliability for categories at largegroup festivals in Kansas varied from .47 (other) to .77 (tone), even with descriptors for each level of achievement (Latimer, Bergee, and Cohen 2010).…”
Section: Reliabilitymentioning
confidence: 96%
“…Several authors have found that judges were often inconsistent in scoring individual captions , even though final ratings demonstrated a high level of interrater reliability (e.g., Burnsed, Hinkle, and King 1985;Latimer, Bergee, and Cohen 2010). These findings suggest that judges might first determine a final rating and then score captions to add up to the predetermined result.…”
Section: Downloaded By [Northeastern University] At 14:27 04 Novembermentioning
confidence: 99%
“…The use of rubrics allows judges to evaluate the performance more reliably (DeLuca and Bolden, 2014;Jonsson and Svingby, 2007). They are helpful in evaluating the performance of persons playing different instruments, at different stages of education (Ciorba and Smith, 2009;Latimer, Bergee and Cohen, 2010).…”
Section: Proposalmentioning
confidence: 99%
“…In educational settings it is agreed assessments should be 'reliable' (measurements of the same skills or knowledge produce the same results), 'consistent' (all skills and knowledge are evaluated by identical procedures), and 'transparent' (assessors and learners all share the same levels of expectation) (Latimer et al, 2010). Increasingly carefully designed assessment rubrics are being used to ensure reliability, consistency and transparency (Ciorba and Smith, 2009 In this English medical course a rudimentary assessment rubric was developed that defined the requirements for specific learning activities in a medical terminology quiz.…”
Section: The Self-reflective Questionnairementioning
confidence: 99%